Decreasing pH, COD and TSS of Domestic Liquid Waste Using Photocatalysis TiO2 (Titanium Dioxide) - Marhadi; Adriansyah, Endi; Herawati, Peppy; Suzana, Asih; Pratama, Aulia Intan (International Journal of Research in Vocational Studies (IJRVOCAS), 2023)
Domestic waste comes from households that must be treated. Based on the Minister of Environment and Forestry Regulation Number P.68/Minister Environment and Forestry-Secretary General/2016 concerning Domestic Wastewater Quality Standards, the government has set a maximum limit for waste water that can be disposed of to the environment or receiving water bodies. includes pH, TSS and COD parameters. This is useful for overcoming the problem of environmental pollution caused by wastewater. Waste water that is not managed properly will have an impact on human health. environmental pollution is harmful to humans. Domestic sewage treatment using a titanium dioxide photocatalyst shows the results of testing the pH value on domestic waste as shown below, showing that overall the concentration of parameters has increased the pH value decrease 90% from acidic to normal with the best pH value with a value of 6.57 at a contact time of 210 minutes of mass catalyst 2.5 grams. Parameter concentration decreased TSS value from initial value of 157 mg/L to normal with the best TSS value of 94 mg/L at contact time of 210 minutes with catalyst mass of 2.5 grams. COD value at contact time of 210 minutes with a mass of 2.5 grams of catalyst with a value of 2861 mg/L. COD value affects the time and mass of the catalyst (1). a decrease of 40.1% where the TSS value meets the quality standard, and the COD value has decreased by 31%. Addition of further processing to get a better COD.